Expert Consultation: Radio-Based Education in the Philippines - McBurnie, Chris (EdTech Hub, 2020)
These slides present an overview of educational radio programming with a particular focus on quality assurance and content design.
ZenodoArchiveID: 3469739 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3469739 2129771:IGCN5KBD 2339240:4DKQGFTT 2405685:25G275PG 2405685:L5TMC4NJ 2405685:YRC7UKWE
Keywords: C:Philippines; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The Role of Interactive Radio Instruction in the COVID-19 Education Response - McBurnie, Chris (Open Development & Education, 2020)
Reading Time: 3 minutes At a time when the COVID-19 pandemic has forced over 1.5 billion students out of school, governments in resource-constrained countries have looked to interactive radio instruction (IRI) to ensure educational continuity. In the past week, we spoke with the Rising Academy Network to consider what an IRI programme could look like and why policymakers have […]
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707808 2405685:PBKNDCEU
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

The role of interactive radio instruction in the coronavirus (COVID-19) education response - McBurnie, Chris (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Every week that passes we see the number of classrooms closed due to COVID-19 increase. During these unprecedented times, the Hub’s mission — to increase the use of evidence-based decisions around EdTech — is more important than ever. We must make sure learning goes on. […]
Library Catalog: edtechhub.org KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707814 2405685:5ZVJ2YZ5
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Monitoring and evaluating radio in education - McBurnie, Chris (EdTech Hub, 2020)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707898 2129771:E77BS5IR 2405685:PLW5MPU5
Keywords: _EdTechHub_Output; dode_eth-src-eth; dode_eth-trf2-dode

From the Helpdesk: Observations and guidance on educational response planning during the COVID-19 crisis (EdTech Hub, 2020)
Written by Rachel Chuang, Tom Kaye, Caitlin Moss Coflan & Arjun Upadhyay (EdTech Hub Helpdesk Management Team) Amid one of the biggest global disruptions to schooling in living memory, countries are quickly developing distance education responses for students. The EdTech Hub’s Helpdesk is providing evidence-informed responses to requests for support from governments and their partners as they face this challenge. …
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707838 2405685:84ZQF884
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Sierra Leone Series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health - McBurnie, Chris; Swaray, Abdulai; Kamara, Bai (EdTech Hub, 2021)
ZenodoArchiveID: 5652005 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652005 2405685:RT5H8XNG
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen

Learning through television in low-income contexts: mitigating the impact of coronavirus (COVID-19) - Watson, Joe (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Written by Joe Watson, research assistant at the University of Cambridge One of the many consequences of COVID-19 is that more than a billion caregivers will soon face the stark (and often scary) realisation that they must become their children’s teachers. This will be particularly difficult in low-income contexts where…
Library Catalog: edtechhub.org KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707800 2339240:ELSHST8I 2339240:NH74Q4D5 2339240:SEDLSMKA 2339240:SRTNHXEM 2339240:ZL8JVQGI 2405685:54S7693K 2405685:BGP7GCNU 2405685:DLE5F2DK 2405685:FF93KYQR 2405685:LA5D6QFR 2405685:PCDTZ7S3 2405685:PD7SX3IX 2405685:SS7E2HN4 2405685:VCLDWRIS 4803016:U4W8F4AZ BGP7GCNU SEDLSMKA
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH